(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The 3D reconstruction of the Central Baths of Nora has required a long and reasoned analysis. On the basis of precise comparisons, a planimetric study of the complex has been first carried out, followed by the more difficult one of the elevations and the roofs, in order to create a model that allows to appreciate the building not only in its structural complexity, but also in the relationship with the spatial context in which it stood. This work represents only a part of a larger project that lead to the creation of a 3D model of the whole central district of Nora.